A review on extraction coupled with analytical techniques used in medicinal plants: torch ginger (Etlingera elatior) / Adibah Aqilah Norddin and Boon Yih Tien - Norddin, Adibah Aqilah; Boon, Yih Tien (2021)
The presence of active compounds in medicinal plants provides physiological effects and acts as a pharmacological agent in preventing and treating diseases since the last decade. This has resulted in an increase of interest in the medicinal plant due to the high demands of the current pharmaceuticals and nutraceuticals industry. However, the extraction parameters will negatively affect the extraction yield due to the degradation of the thermosensitive compounds. Therefore, it is very crucial to develop an effective and selective method for the extraction, separation and isolation of those bioactive compounds, especially from unexplored plants. Torch ginger is an unexplored medicinal plant that serves benefits on human health including medicament for cardiovascular diseases and cancer. This review intends to provide a comprehensive insight into the variety of extraction methods coupled with analytical techniques on torch ginger with a view to identify novel active compounds for global health benefits. This review will discuss the main parameters involved such as time, temperature, solvent, and sample pre-treatment. It is found that conventional extraction techniques are being replaced by non-conventional techniques to reduce energy and solvent consumption, increase efficiency and selectivity, and meet environmental regulations. The chromatography technique prevails in others due to its separation efficiency. However, the lab-intensive and time-consuming extraction, separation and isolation process has been the bottleneck for the bioactive compounds in pharmaceutical development. Further investigation is needed to improve the extraction, separation and isolation technique to maximize yields and reduce degradation associated with environmental concern and costs.